DERIVATIF RADIAL ANOMALI GRAVITASI UNTUK IDENTIFIKASI ZONA SESAR - Ronodirdjo, Muhammad Zuhdi; Doyan, Aris; Sutrio, Sutrio; Wahyudi, Wahyudi; Makhrus, Muh (Kappa Journal, 2019)
Fault is a displacement of the land with a certain direction and shift that triggers an earthquake. The existence of faults that are not visible on the surface can be identified by measuring the gravity anomaly above the earth's surface around the fault zone. This study was conducted with the aim of testing the effectiveness of radial derivatives for identification of fault zones, i.e the presence and positions of faults. Radial derivative is a horizontal derivative of the earth's gravity anomaly value with the radial direction away from a certain point that is considered as the radial center. Gravity anomaly data used in this study is synthetic data from computer calculations using the principle of forward modeling from a fault model. This model is in the form of a displacement of the rocks making up the soil at a depth of 100 m with a vertical shift direction of 4 m with an area of the fault zone 600 m x 600 m or 360,000 m2. This synthetic gravity data is then performed a radial derivative treatment. The results of this study show that radial derivatives are able to identify the presence and position of the fault.